1995
DOI: 10.1007/bf01900601
|View full text |Cite
|
Sign up to set email alerts
|

Malpuech facial clefting syndrome in a Japanese boy with cardiac defects

Abstract: SummaryWe reported on a Japanese boy similar to the patients previously reported by Malpuech et al. (1983) with mental and growth retardation, hypertelorism, bilateral cleft lips, cleft palate, and urogenital anomalies. He also had undescribed cardiac defects. This is probably the second case report of Malpuech facial clefting syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 1 publication
0
18
0
Order By: Relevance
“…For Malpuech syndrome, data from all earlier reported patients were used [Malpuech et al, 1983;Chinen and Naritomi, 1995;Guion-Almeida, 1995;Crisponi et al, 1999;Kerstjens-Frederikse et al, 2005], although it seems well possible that Patient 2 reported by Guion-Almeida has in fact Wolf-Hirschhorn or Pitt-Rogers-Danks syndrome [Selicorni and Faravelli, 2000]. The single patient reported in an abstract [Hall, 2004] could not be used due to lack of sufficiently detailed data.…”
Section: Discussionmentioning
confidence: 99%
“…For Malpuech syndrome, data from all earlier reported patients were used [Malpuech et al, 1983;Chinen and Naritomi, 1995;Guion-Almeida, 1995;Crisponi et al, 1999;Kerstjens-Frederikse et al, 2005], although it seems well possible that Patient 2 reported by Guion-Almeida has in fact Wolf-Hirschhorn or Pitt-Rogers-Danks syndrome [Selicorni and Faravelli, 2000]. The single patient reported in an abstract [Hall, 2004] could not be used due to lack of sufficiently detailed data.…”
Section: Discussionmentioning
confidence: 99%
“…A few cases of Malpuech syndrome have been reported [Malpuech et al, 1983;Guion-Almeida et al, 1995;Chinen and Naritomi, 1995]. In our opinion, facial gestalt of these, in particular patient 1 reported by Crisponi et al [1999] and patient 3 of Guion-Almeida et al [1995], resembles the Wolf-Hirschorn/Pitt-RogerDanks (WHS/PRDS) facial phenotype.…”
Section: To the Editormentioning
confidence: 52%
“…In the patients described by Guion-Almeida [1995], omphalocele, umbilical hernia, caudal appendage, and hearing loss were also present. The patient described by Chinen and Naritomi [1995] also showed ventricular septal defect, skin dimples at elbows and knees, ribs and vertebral anomalies, wormian bones at the lambdoid suture, short left fifth finger middle phalanx, and absence of left kidney. The phenotypic findings in the first-born, particularly the saddle scrotum, led us to consider the diagnosis of Aaskorg syndrome [Aaskorg, 1970].…”
Section: Discussionmentioning
confidence: 89%
“…Malpuech et al [1983] first described the syndrome in 4 sibs in one gypsy family. Subsequently, Chinen and Naritomi [1995] and Guion-Almeida [1995] reported 4 additional patients. Here, we report on 2 brothers with this clinical condition.…”
Section: Introductionmentioning
confidence: 98%